Partial discharge characteristics in polyethylene using pulse shape and pulse sequence analysis - Arief , Y. Z. (IEEE Explore, 2007)
The paper describes the analysis of partial discharge characteristics of polyethylene by means of the pulse shape and pulse sequence analysis. A needle-plane electrode configuration and a ramped sinusoidal AC-voltage were utilized to generate internal discharges. The Pulse Sequence Analysis uses the correlations between consecutive discharges and allows better diagnostics e.g. by analyzing the time differences between consecutive discharge events or the corresponding changes of the external voltage. It is found that the discharge characteristics change during the growth of an electrical tree. Furthermore the analysis suggested that space charges around the tip of the needle electrode generated by the partial discharge events play an important role. Compared with the conventional evaluation method on the base of the phase angles of occurrence, the pulse sequence analysis has proven to be a powerful tool to investigate partial discharges and order to gain a better understanding of the discharge phenomena in polymeric insulating materials and other insulation systems. Different types of partial discharges can be identified. Especially the PD characteristic during electrical tree growth in polyethylene will be discussed.